PUERPERAL SEPSIS -STILL A MAJOR THREAT FOR PARTURIENT - Shamshad, Shamshad; Shamsher, Saadia; Rauf, Bushara (Journal of Ayub Medical College Abbottabad, 2010)
Background: Puerperal sepsis is one of the leading causes of preventable maternal morbidity and mortality. It is still ranked as 3rd major cause of maternal deaths in our country. The objective of this study was to evaluate morbidity and mortality from puerperal sepsis and to identify its risk factors. Methods: This observational study was carried out in Ayub Teaching Hospital over a period of three years. All patients admitted with diagnosis of puerperal sepsis secondary to genital tract infection were evaluated with thorough details of history and examination to determine their demographic details, obstetrical profiles, presenting features, state of infectious morbidity, need for intervention and mortality related to puerperal sepsis. Results: Puerperal sepsis was 1.7% of all obstetrical admissions and 34.4% of postnatal complications. It was seen common among young patients of 15-25 years age, 61 (66.3%), of lower parity, 58 (63.00%), low socioeconomic status, 60 (65.20%), uneducated patients, 72 (78.20%), home deliveries, 68 (73.90%), prolong labour, 54 (58.60), prolong rupture of membranes from 48-72 hours, 68 (73.8%) and deliveries conducted by untrained birth attendants, 57 (60.5%). Puerperal sepsis morbidity was mostly foul smelling discharge, 23 (25%), retained product of conception, 41 (44.5%), peritonitis, 8 (8.60%), septicaemia, 4 (4.3%), pelvic abscess, 10 (10.80%), endotoxic shock, 4 (4.30%), disseminated intravascular coagulation, 2 (2.1%). Sepsis related mortality was 6/42 (14.2%). Conclusion: Puerperal sepsis is an important public health problem contributing to maternal morbidity and mortality. Majority of predisposing factors are preventable. Optimal antiseptic measures and careful monitoring are needed throughout the process of labour. Keywords: Puerperal sepsis, Maternal mortality, Rupture of membranes, Obstructed labour, Traditional birth attendant, TBA, disseminated intravascular coagulation, DIC